A combined experimental and theoretical investigation on the Cu(II) sensing behavior of a piperazinyl moiety based ligand, and catecholase and biological activities of its Cu(II) complex in combination with pyridine 2, 5-dicarboxylate. (28th January 2016) - Mistri, Soumen; Paul, Aparup; Bhunia, Apurba; Manne, Rajesh Kumar; Santra, Manas Kumar; Puschmann, Horst; Manna, Subal Chandra
Graphical abstract: A Cu(II) fluorescent chemosensor, 6-methoxy-2-[2-(1-piperazinyl)ethylimino]methylphenol (HL), has been synthesized and characterized by spectral studies. HL shows high selectivity for Cu(II) with 24.87 μM fluorometric detection limit and the sensing behavior of HL was explained by DFT/TDDFT calculations. Abstract: A Cu(II) fluorescent chemosensor, 6-methoxy-2-[2-(1-piperazinyl)ethylimino]methylphenol (HL), has been synthesized and characterized by FT-IR, NMR, electronic absorption and emission spectral studies. HL shows high selectivity for Cu(II) over a range of other metal ions. HL has a 24.87 μM ( R 2 = 0.9959) fluorometric detection limit for Cu(II), which is very close to the maximum allowable level of Cu(II) in drinking water as recommended by US EPA. Theoretical calculations at the B3LYP level revealed that the formation of a five-coordinated complex in solution is responsible for the observed sensing behavior. The binding constant for the 1:1 complex between Cu(II) and HL was determined using fluorescence titration, and the calculated value is 0.4 liter/mol. Using HL, [Cu(HL)(pdc)(H2 O)]·[Cu(HL)(pdc)]·10.5(H2 O) (1 ) (pdc = pyridine 2, 5-dicarboxylate) has been synthesized and structurally characterized. Complex1 is active for catalyzing aerobic oxidation of 3, 5-di-tert butyl catechol (3, 5-DTBC) to 3, 5-di-tert butyl benzoquinone (3, 5-DTBQ). Anticancer activity of1 in human breast (MCF7) cancer cell lines reveals dose dependent suppression of cell viability with IC50 value 47 ± 5.2 μM.